Kesalahan penulisan singkatan dan akronim pada akun Twitter @collegemenfess - Aden, Salsabila (Maliki Interdisciplinary Journal, 2024)
This study aims to find out language errors in writing abbreviations and acronyms on the Twitter account @collegemenfess. This article uses a qualitative descriptive approach by observing and noting. The research object studied in this article is language errors in writing abbreviations and acronyms in posts on the Twitter account @collegemenfess. The results of the analysis that have been found amount to 15 data, namely in the form of 14 data errors in writing abbreviations and 1 data errors in writing acronyms.